Numerical Investigation of the Production Behavior of Methane Hydrates under Depressurization Conditions Combined with Well-Wall Heating - Xuke Ruan; Xiao-Sen Li; Chun-Gang Xu (Energies, 2017)
In this study, a 2D hydrate dissociation simulator has been improved and veriﬁed to be valid in numerical simulations of the gas production behavior using depressurization combined with a well-wall heating method. A series of numerical simulations were performed and the results showed that well-wall heating had an inﬂuence enhancing the depressurization-induced gas production, but the inﬂuence was limited, and it was even gradually weakened with the increase of well-wall heating temperature. Meanwhile, the results of the sensitivity analysis demonstrated the gas production depended on the initial hydrate saturation, initial pressure and the thermal boundary conditions. The supply of heat for hydrate dissociation mainly originates from the thermal boundaries,whichcontrolthehydratedissociationandgasproductionbydepressurizationcombined with well-wall heating. However, the effect of initial temperature on the gas production could be nearly negligible under depressurization conditions combined with well-wall heating.